Lack of Association Between Shape and Volume of Subcortical Brain Structures and Restless Legs Syndrome - Hermesdorf, Marco; Sundermann, Benedikt; Rawal, Rajesh; Szentkirályi, András; Dannlowski, Udo; Berger, Klaus (Frontiers in Neurology, 2018)
Objective: Previous studies on patients with Restless Legs Syndrome (RLS) yielded inconclusive results in the MRI-based analyses of alterations of subcortical structures in the brain. The aim of this study was to compare volumes as well as shapes of subcortical structures and the hippocampus between RLS cases and controls. Additionally, the associations between the genetic risks for RLS and subcortical volumes were investigated. Methods: We compared volumetric as well as shape differences assessed by 3 tesla magnetic resonance imaging in the caudate nucleus, hippocampus, globus pallidus, putamen and thalamus in 39 RLS-cases versus 117 controls, nested within a population-based sample. In a subsample, we explored associations between known genetic risk markers for RLS and the volumes of the subcortical structures and the hippocampus. Results: No significant differences between RLS-cases and controls in subcortical and hippocampal shapes and volumes were observed. Furthermore, the genetic risk for RLS was unrelated to any alterations of subcortical and hippocampal gray matter volume. Interpretation: We conclude that neither RLS nor the genetic risk for the disease give rise to changes in hippocampal and subcortical shapes and gray matter volumes.